Repeated measurements of cerebral blood flow in the left superior temporal gyrus reveal tonic hyperactivity in patients with auditory verbal hallucinations: a possible trait marker - Homan, Philipp; Kindler, Jochen; Hauf, Martinius; Walther, Sebastian; Hubl, Daniela; Dierks, Thomas (Frontiers in Human Neuroscience, 2013)
Background: The left superior temporal gyrus (STG) has been suggested to play a key role in auditory verbal hallucinations in patients with schizophrenia. Methods: Eleven medicated subjects with schizophrenia and medication-resistant auditory verbal hallucinations and 19 healthy controls underwent perfusion magnetic resonance imaging with arterial spin labeling. Three additional repeated measurements were conducted in the patients. Patients underwent a treatment with transcranial magnetic stimulation (TMS) between the first 2 measurements. The main outcome measure was the pooled cerebral blood flow (CBF), which consisted of the regional CBF measurement in the left superior temporal gyrus (STG) and the global CBF measurement in the whole brain. Results: Regional CBF in the left STG in patients was significantly higher compared to controls (p < 0.0001) and to the global CBF in patients (p < 0.004) at baseline. Regional CBF in the left STG remained significantly increased compared to the global CBF in patients across time (p < 0.0007), and it remained increased in patients after TMS compared to the baseline CBF in controls (p < 0.0001). After TMS, PANSS (p = 0.003) and PSYRATS (p = 0.01) scores decreased significantly in patients. Conclusions: This study demonstrated tonically increased regional CBF in the left STG in patients with schizophrenia and auditory hallucinations despite a decrease in symptoms after TMS. These findings were consistent with what has previously been termed a trait marker of auditory verbal hallucinations in schizophrenia.